The effect of debt restructuring scheme on the performances of Malaysian firms - Azman, Sariati (2003)
Previous studies have found that the out-of-court restructuring strategy was one of the most preferred restructuring exercises practised during the 1997 Asian financial crisis (see Haley, 2000; Mako, 2001). The out-of-court strategy is a strategy that involves negotiation between a company, its creditors and other related parties to find the best solution for the company's debt problems without having to resort to legal proceedings. This strategy seems popular, as many Asian countries have adopted it. In Malaysia, such a strategy is facilitated by the Corporate Debt Restructuring Committee (CDRC). Although the progress of the CDRC is very encouraging (see Chotigeat and Lin, 2001; Nor Azimah, 2001), the effect of the scheme on the companies has never been tested. Therefore, this study has examined the effect of the CDRC's debt restructuring scheme on the companies' performances based on seven public listed companies which had successfully completed the scheme by the year 2000. This study have analysed two areas, i.e., the companies' capital structures (using six leverage ratios) and the companies' financial performances (using three profitability ratios). The hypotheses of this study are that (a) there will be a significant decrease in the companies' leverage ratios after the restructuring process, and (b) there will be a significant increase in the companies' profitability ratios after the restructuring process. Based on the paired sample t-test, the Wilcoxon matched-pairs signed rank test and the effect size test, the study finds little evidence to support the hypothesis on the capital structures but finds sufficient evidence to support the hypothesis on the financial performances. Thus, this study concludes that the scheme did not greatly improve the companies' capital structures, but did improve the companies' financial performances.